Learning to Classify the Consumer Conﬁdence Indicator (in Portugal) - Caleiro, António Bento (2021)
The literature paid some attention, some time ago, to the relationship that, supposedly, should exist between the level of consumer conﬁdence and the unemployment rate. This relationship is interesting, both from a scientiﬁc point of view, given the inherently subjective character of that level of conﬁdence, but also from the point of view of economic policy, given the importance of the unemployment rate. In this article, that relationship is revisited, using learning models, namely regression and classiﬁcation trees. Using, for example, the case of Portugal, the unemployment rate presents itself as an adequate classiﬁer of the consumer conﬁdence level. The use of classiﬁcation trees shows that the separation between low and high values of the consumer conﬁdence indicator is made from an adequate threshold value of the unemployment rate. The use of regression trees shows that the levels of consumer conﬁdence are inversely related to the levels of the unemployment rate. In terms of policy lessons, this conﬁrms that, in the face of economic crises, such as the one we are experiencing, in which conﬁdence levels tend to fall and the unemployment rate increases, the relationship between these two variables cannot be ignored.